Digital multiplexing techniques - Shah, Asadullah; Shaikh, Asadullah (IIUM Press, 2011)
Multiplexing techniques are broadly classified as analogue and digital, digital being the latest. Time Division Multiplexing (TDM) and Statistical TOM are most commonly used digital multiplexing techniques. The TOM is a detenninistic method of multiplexing various sources in pre-determined fixed slots. Statistical TDM, (STDM) uses dynamic method of allocating time slots to only the active users. The dynamic nature of slot allocations enhances bandwidth utilization better than TDM however this property of STDM is always suitable for non-delay sensitive systems. For real-time and delay sensitive systems the TDM approach is the better option